The Role of Business Advisors and Project Management Offices in Strengthening Public Sector Accounting Systems in the KDKMP Program - Ayu Kurnia Sari; Renny Maisyarah; Aulia; Siti Arifah (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The Business Advisor serves as a strategic partner, guiding financial management, planning, and human resource capacity building. The Project Management Office (PMO) ensures program implementation proceeds according to plan through monitoring, evaluation, and risk mitigation. However, the practical implementation of the Business Advisor and PMO roles often faces challenges. Key obstacles include limited understanding of public sector accounting standards among village officials, a lack of coordination in program implementation, and a lack of evaluation instruments capable of assessing the effectiveness of public sector accounting implementation in the field. The result is that the Business Advisor (BA) plays a crucial role in strengthening the public sector accounting system through technical assistance, needs analysis, and recommendations tailored to the context of regional bureaucracy. The BA helps ensure that the implementation of the Government Accounting System (SAP) and financial management mechanisms are standardized, accurate, and accountable.  The Project Management Office (PMO) plays a strategic role in coordinating all stages of the KDKMP Program, from planning, control, monitoring, and evaluation. The PMO ensures that all activities related to strengthening the accounting system are on schedule, integrated, and meet quality standards.